Avaliação de efeitos de um extrato aquoso de cinnamomum zeylanicum L. na marcação de constituintes sanguíneos com tecnécio-99m e na morfologia das hemácias de ratos wistar - Benarroz, Mônica de Oliveira (2007)
Radiobiocomplexes are used to obtain images in nuclear medicine and employed in basic research. Blood constituents labeled with technetium-99m (99mTc) have also been employed as radiobiocomplexes and used also experimental model for evaluation of the biological effects of natural or synthetic drugs. The analysis of the morphology and the morphometrics parameters (perimeter/área ratio) can be used to evaluate the effects of drugs upon the structure of the membrane of red blood cells. Cinnamomum zeylanicum (cinnamon) is a spice used as herbal medicine to treat diseases. The aim of this study was to evaluate the effect of in vitro and in vivo treatment with an aqueous cinnamon extract on the labeling of blood constituents with 99mTc and on the morphology of red blood cells from Wistar rats. In the in vitro treatment, isolated blood sample from animals were incubated with cinnamon extract. In the in vivo treatment, blood samples were also withdrawn from animals treated with cinnamon extract. In both cases, the radiolabeling of blood constituents was done. The morphological analysis of red blood cells was also done. As control, blood or animals treated with NaCl 0.9%. The data obtained on the labeling of blood constituents with 99mTc experiments indicated that the in vitro treatment with cinnamon extract was capable to decrease signiicantly (p<0.05) the percentage of radioactivity in cellular compartments and on the fixation of cellular and plasma proteins. These effects were not observed on the in vivo treatment. The results obtained for the morphology of red blood cells suggest that the in vitro and in vivo treatments did not alter the morphology and the perimeter/area ratio. The in vitro treatment with aqueous cinnamon extract could affect the membrane structures related with the oxidation status of the stannous ion pertechnetate ion, altering the labeling of blood constituentes with 99mTc. This study was a multidisciplinary experimental research. It was developed with the contribution of the different Departments and Services of the Hospital Universitário Pedro Ernesto of the Universidade do Estado do Rio de Janeiro